2015
DOI: 10.1155/2015/780983
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Sperm DNA Toroid Integrity Test and Risk of Miscarriage

Abstract: Current methods of analyzing sperm chromatin competency overlook the inner sperm compartment which is inaccessible to probes and reagents. By breaking the molecular protamine disulfide bridges, the DNA toroids are exposed to integrity analysis. The aim was to develop a simple nuclear toroid test and determine its association with fertilization, pregnancy, and miscarriage. The approach involved treating washed sperm remaining after ICSI procedures (N = 35 cases) with acidified Triton X-100 and dithiothreitol (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…The ability of these staining methods to identify alterations in chromatin status is demonstrated by higher percentages of stained mouse sperm under different conditions, such as treatment with estrogens (30%) [46], oxidative stress, age (30-70%) [47], and protamine 1 (90%) or protamine 2 deficiencies (30%) [48]. In comparison to other species, alterations in chromatin status in the mouse are rather low; studies of human, bull, boar, dog, and cat sperm revealed higher proportions of spermatozoa with defects in sperm chromatin compaction [39,42,55,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of these staining methods to identify alterations in chromatin status is demonstrated by higher percentages of stained mouse sperm under different conditions, such as treatment with estrogens (30%) [46], oxidative stress, age (30-70%) [47], and protamine 1 (90%) or protamine 2 deficiencies (30%) [48]. In comparison to other species, alterations in chromatin status in the mouse are rather low; studies of human, bull, boar, dog, and cat sperm revealed higher proportions of spermatozoa with defects in sperm chromatin compaction [39,42,55,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%